THE EXCEPTIONAL ACTIVITY AND GROWTH OF THE SOUTHEAST CRATER, MOUNT ETNA (ITALY), BETWEEN 1996 AND 2001 - Behncke B.; Neri M.; Pecora E.; Zanon V. (My University, 2006)
Between 1971 and 2001, the Southeast Crater was the most productive of the four summit craters of Mount Etna, with activity that can be compared, on a global scale, to the opening phases of the Pu‘u ‘Ō‘ō-Kūpaianaha eruption of Kīlauea volcano, Hawai‘i. The period of highest eruptive rate was between 1996 and 2001, when near-continuous activity occurred in five phases. These were characterized by a wide range of eruptive styles and intensities from quiet, non-explosive lava emission to brief, violent lava-fountaining episodes. Much of the cone growth occurred during these fountaining episodes, totaling 105 events. Many showed complex dynamics such as different eruptive styles at multiple vents, and resulted in the growth of minor edifices on the flanks of the Southeast Crater cone. Small pyroclastic flows were produced during some of the eruptive episodes, when oblique tephra jets showered the steep flanks of the cone with hot bombs and scoriae. Fluctuations in the eruptive style and eruption rates were controlled by a complex interplay between changes in the conduit geometry (including the growth of a shallow magma reservoir under the Southeast Crater), magma supply rates, and flank instability. During this period, volume calculations were made with the aid of GIS and image analysis of video footage obtained by a monitoring telecamera. Between 1996 and 2001, the bulk volume of the cone increased by ~36×106 m3, giving a total (1971–2001) volume of ~72×106 m3. At the same time, the cone gained ~105 m in height, reaching an elevation of about 3,300 m. The total DRE volume of the 1996–2001 products was ~90×106m3. This mostly comprised lava flows (72×106 m3) erupted at the summit and onto the flanks of the cone. These values indicate that the productivity of the Southeast Crater increased fourfold during 1996–2001 with respect to the previous 25 years, coinciding with a general increase in the eruptive output rates and eruption intensity at Etna. This phase of intense summit activity has been followed, since the summer of 2001, by a period of increased structural instability of the volcano, marked by a series of important flank eruptions.
Keywords: MOUNT ETNA; LAVA FOUNTAINING; MICROPLINIAN; REMOTE VIDEO MONITORING; VOLUME CALCULATIONS; CONE GROWTH